The Impact of LINKS (Local and Indigenous Knowledge Systems) on Human Resources Innovation Capability Strategy and Business Performance of Food and Beverage MSMEs (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
The low innovation capability of a country is in line with the low innovation capabilities of economic institutions and organizations including MSMEs in it. For companies such as MSMEs, innovation has the power to build competitive advantages in sources of prosperity and economic growth. One of the factors driving the creation of an innovation climate in organizations is culture. Therefore, it is necessary to have a LINKS (Local and Indigenous Knowledge Systems) based approach which refers to the understanding, skills, culture, and philosophy developed by the community with a long history of interaction with the natural environment of the community itself. This paper aims to analyze the impact of LINKS on Human Resources Innovation Capability Strategy and Business Performance of Food and Beverage MSMEs. This research shows that LINKS (Local Indigenous Knowledge System) indicators had a positive and significant effect on all factors of Innovation Capabilities. Therefore, this study shows that LINKS (Local and Indigenous Knowledge Systems) can encourage Human Resources Innovation Capability Strategy and has implications for increasing Innovation Activities and Innovation Performance to improve the Business Performance of food and beverage MSMEs in Jogjakarta.